INOVASI KURIKULUM PENDIDIKAN ISLAM DI MADRASAH IBTIDAIYAH BERBASIS PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN KOMPETENSI ABAD 21 - Koko Winata; Kania Dewi; Rizwan Martiadi; Afeefa Binti Aminuddin; Edy Sofyan (MURABBI, 2026)
This study aims to analyse innovations in the Islamic education curriculum at Madrasah Ibtidaiyah based on collaborative learning in improving the quality of learning and students’ twenty-first-century competencies. The study employed a qualitative approach using the library research method. Data were obtained from accredited national journals, international journals, academic books, and educational policy documents relevant to the last five years. Data collection techniques were conducted through a systematic literature review, while data analysis employed thematic analysis through data reduction, categorisation, interpretation, and conclusion drawing. The findings indicate that curriculum innovation based on collaborative learning is capable of creating more active, participatory, and contextual learning processes in Madrasah Ibtidaiyah. This approach contributes to the enhancement of communication skills, collaboration, academic literacy, as well as the strengthening of Islamic values and students’ character development. The integration of digital technology also supports learning effectiveness and broadens access to learning resources. However, the implementation of curriculum innovation still faces several challenges, including limited teacher competence, inadequate infrastructure, and low levels of digital literacy. Therefore, strengthening teachers’ capacities and institutional support is necessary to ensure the optimal implementation of a collaborative learning-based curriculum.